Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
Keywords: dept.swk